Post‐mastectomy surveillance of BRCA1/BRCA2 mutation carriers: Outcomes from a specialized clinic for high‐risk breast cancer patients. Issue 5 (11th February 2021) - Kanana, Nayroz; Ben David, Meirav A.; Nissan, Noam; Yagil, Yael; Shalmon, Anat; Halshtok, Osnat; Gotlieb, Michael; Faermann, Renata; Klang, Eyal; Samoocha, David; Yassin, Mohammad; Davidson, Tima; et al.
Abstract: Female BRCA1 / BRCA2 mutation carriers may elect bilateral risk‐reducing mastectomy. There is a paucity of data on yield of imaging surveillance after risk‐reducing mastectomy. This retrospective study focused on female BRCA1 / BRCA2 mutation carriers who underwent bilateral mastectomy either as primary preventative, or as secondary preventative, after breast cancer diagnosis. All participants underwent breast imaging at 6‐ to 12‐month intervals after mastectomy. Data on subsequent breast cancer diagnosis and timing were collected and compared between the groups. Overall, 184 female mutation carriers (134 BRCA1, 45 BRCA2, 5 both BRCA genes) underwent bilateral mastectomy after initial breast cancer diagnosis, between April 1, 2009 and August 31, 2018. During a mean follow‐up of 6.2 ± 4.2 years, 13 (7.06%) were diagnosed with breast cancer; 12 ipsilateral (range: 0.4–28.8 years) and 1 contralateral breast cancer, 15.9 years after surgery. On the contrary, among asymptomatic BRCA1 ( n = 40) and BRCA2 ( n = 13) mutation carriers who underwent primary risk‐reducing mastectomy (mean age at surgery 39.5 ± 8.4 years); none has developed breast cancer after a mean follow‐up of 5.4 ± 3.4 years. BRCA1 / BRCA2 mutation carriers with prior disease who underwent risk‐reducing mastectomy after breast cancer diagnosis are still prone for developing ipsi or contralateral breast cancer, and therefore may benefit from continues clinical and imaging surveillance, unlike BRCA1 / BRCA2 mutation carriers who undergo primary preventative bilateral mastectomy.